ARTISTIC EXPRESSION OF THE BLOCKADE THEME IN O. BERGHOLTZ’S LYRICS - Kalmuratova R. O. (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes the ontological and adverbial levels of the theme of the blockade in O. Bergholz’s lyrics.